COVID-19 disease in professional football players: symptoms and impact on pulmonary function and metabolic power during matches - Gattoni, C.; Conti, E.; Casolo, A.; Nuccio, S.; Baglieri, C.; Capelli, C.; Girardi, M. (Physiological Reports, 2022)
This study aimed at: (1) Reporting COVID-19 symptoms and duration in professional football players; (2) comparing players` pulmonary function before and after COVID-19; (3) comparing players` metabolic power (Pmet) before and after COVID-19. Thirteen male players (Age: 23.9 ± 4.0 years, VO2peak: 49.7 ± 4.0 mL/kg/min) underwent a medical screening and performed a running incremental step test and a spirometry test after COVID-19. Spirometric data were compared with the ones collected at the beginning of the same season. Players` mean Pmet of the 10 matches played before COVID-19 was compared with mean Pmet of the 10 matches played after COVID-19. Players completed a questionnaire on COVID-19 symptoms and duration 6months following the disease. COVID-19 positivity lasted on average 15 ± 5 days. "General fatigue" and "muscle fatigue" symptoms were reported by all players during COVID-19 and persisted for 77% (general fatigue) and 54% (muscle fatigue) of the players for 37 ± 28 and 38 ± 29 days after the disease, respectively. No significant changes in spirometric measurements were found after COVID-19, even though some impairments at the individual level were observed. Conversely, a linear mixed-effects model analysis showed a significant reduction of Pmet (-4.1 ± 3.5%) following COVID-19 (t = -2.686, p < 0.05). "General fatigue" and "muscle fatigue" symptoms may persist for several weeks following COVID-19 in professional football players and should be considered for a safer return to sport. Players` capacity to compete at high intensities might be compromised after COVID-19.